Evaluating dairy sheep systems for conversion to the optimized agroecological model - Ruíz F.A.; Mena Y.; Manca C.; Sitzia M. (Innovation for sustainability in sheep and goats, 2019)
Interest is growing in promoting sustainable animal production systems because of their healthy relation to the natural environment. Ecological systems stand out, as they pay special attention to preserving natural resources, promoting biodiversity, guaranteeing animal well-being, and obtaining healthy products from raw materials and natural processes. The objective of this study is to evaluate proximity to the agroecological model of dairy sheep systems in Sardinia, Italy. Based on the methodology described by Mena et al (2012) for goat milk systems, a questionnaire was designed for dairyfarms, including 55 variables integrated into 9 indicators. Twenty-two dairy sheep farms were surveyed, all farms with Sarda breed. The results show that farms are close to this agroecological model, necessitating some changes in aspects related to: i) use more sustainable products for the cultivation of forages and grains; ii) improve farm management and data collection and iii) increase the autonomy in products sales.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)